ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU BATANG KELAPA PADA INDUSTRI MEBEL DAN BAHAN BANGUNAN (Studi Kasus Pada BLPT GMIM Kaaten Tomohon) - Kevin Lentin Montolalu; Noortje M. Benu; Lyndon R.J. Pangemanan (Sam Ratulangi University, 2018)
This study aims to analyze the inventory of coconut raw materials on funiture industry and materals building in BLPT GMIM Kaaten Tomohon. This research was conducted for three months, from June until Agugust 2017. The data used in this research is primary data and secondary data. Primary data was obtained through interviews to company managers, while secondary data was obtained from data that has been compiled in the from of documents from the company, literature and internet. The data is processed using EOQ (Economic Order Quantity) method. Result showed that the control policy of raw material inventory in BLPT GMIM Kaaten Tomohon has not been efficient, it is indicated by the company’s inventory cost is bigger than the result of EOQ analysis method.*lrr*